Early and late pulmonary effects of nebulized LPS in mice: An acute lung injury model - de Souza Xavier Costa, Natália; Ribeiro Júnior, Gabriel; dos Santos Alemany, Adair Aparecida; Belotti, Luciano; Zati, Douglas Hidalgo; Frota Cavalcante, Marcela; Matera Veras, Mariana; Ribeiro, Susan; Kallás, Esper Georges; Nascimento Saldiva, Paulo Hilário; Dolhnikoff, Marisa; Ferraz da Silva, Luiz Fernando (PloS one, 2017)
Acute respiratory distress syndrome (ARDS) has a high mortality rate of 35-46% depending on its severity. Animal models are crucial to better understand the pathophysiology of diseases, including ARDS. This study presents a feasible animal model of acute lung injury (ALI) using nebulized lipopolysaccharide (LPS) in a non-invasive approach, focusing on its short and long-term effects. Mice received nebulized LPS or vehicle only (control group). Blood, BALF and lung tissue were collected 24 hours (LPS 24h) or 5 weeks (LPS 5w) after the nebulized LPS-induced lung injury. Inflammatory cytokines were assessed in the blood serum, BALF and lung tissue. Stereological analyses and remodeling changes were assessed by histology and immunohistochemistry at the specified time points. The LPS 24h group showed increased pro-inflammatory cytokine levels, intense cell influx, increased total septal volume, septal thickening and decreased surface density of the alveolar septa. The LPS 5w group showed persistent lung inflammation, septal thickening, increased total lung volume, accentuated collagen deposition, especially of collagen type I, and decreased MMP-2 protein expression. We present a feasible, reproducible and non-invasive nebulized-LPS animal model that allows the assessment of both the acute and late phases of acute lung injury. The presence of lung remodeling with collagen deposition after 5 weeks makes it useful to study the pathophysiology, complications, and possible therapeutic intervention studies that aim to understand and reduce pulmonary fibrosis in the late phases of ALI.